Synaptotagmin genes expression profiling in single pancreatic α and β-cell. - Tan, Sijie. (2011)
Gene expressions of synaptotagmins were characterized up to the resolution of pancreatic islets till date. However, it is unknown whether the synaptotagmin expressions identified were the results of α and/or β-cells transcription activities. Hence, we used a two-cycle multiplex and semi-nested PCR amplification procedure to first identify gene expressions of synaptotagmin isoforms I-X in mouse single pancreatic pseudo-islet, then increasing the resolution to single pancreatic α and β-cell. Our study detected the gene expressions of synaptotagmins V, VII and IX at the pseudo-islet level, and demonstrated that α-cells express synaptotagmins VII and IX, while β-cells express synaptotagmin VII. Based on the transcript abundance of synaptotagmin isoforms, we suggest that synaptotagmin VII is the principal Ca2+ sensor in Ca2+-dependent glucagon and insulin exocytosis in α and β-cells. We also characterized the gene expressions of synaptotagmin isoforms I-X in αTC-1 cells subjected to prolonged hyperglycemia, as a model to study synaptotagmin genes expression in pancreatic α-cells in Type II Diabetes Mellitus. We demonstrated that synaptotagmins III and VII genes expression were significantly up-regulated during hyperglycemia. Hence, we propose a hyperglycemia-induced stimulus-secretion coupling model in αTC-1 cells to account for this behaviour.